(untitled) (American Journal of Education and Technology, 2023)
The lack of technical support and maintenance impedes to the utilization of ICT resources in schools. As part of the government’s commitment to achieve the goals embedded in the country’s vision 2020, a number of schools have been beneficiaries of ICT facilities like computers, printers, laptops, LCD projectors, and speakers through the Department of Education Computerization Program (DCP). This descriptive-correlational research study assesses the status of the maintenance and support system of ICT resources in public elementary schools in the District of San Jose, Northern Samar, Philippines. Results revealed that school heads, ICT coordinators, and teachers were least satisfied of ICT maintenance procedure. In the same manner that the school heads, ICT coordinators and teachers support system were moderately satisfactory. There were significant differences in the maintenance procedures among the respondents particularly in replacing or repairing the faulty components and upgrading hardware and software. This concludes varied ways in which the respondents respond to the maintenance of faulty components and upgrading the hardware and software. Furthermore, difference on the technical support workload and technology integration among the three groups of respondents appeared to vary in terms of support system. The finding singles out the varied compliance of the respondents in technical support and technology integration.